The Dispute Board as an Alternative to the Construction Service Disputes Settlement - Fadia Fitriyanti; Emil Adli (Proceedings International Conference on Sustainable Innovation (ICoSI), 2021)
Dispute settlement through the dispute board is an alternative to settling new disputes that are not regulated in LawNumber 30 of 1999 concerning Arbitration and APS. The specific objectives to be achieved in this study to look fordata and examine the forms of construction service disputes that are resolved using the dispute board. This research isnormative juridical research. Primary data were obtained through an interview with the Head of Sub Directorate of JBH(Freeway). Secondary data were obtained from documents in the research location above. Data analysis methods usedin this study are statutory approaches and conceptual approaches. The research was analytical descriptive. The forms ofDispute Construction Services using the Dispute board can be seen in various criteria.